Response of the Arab Donors to the Global Financial Crisis and the Arab Spring - Rouis, Mustapha (World Bank, Washington, DC, 2014)
Development assistance from Gulf Cooperation Council (GCC) countries and Arab financial institutions has been responsive in addressing development and humanitarian needs in many developing countries. Since the global financial crisis (2008-2011), the combined net official development assistance (ODA) from Kuwait, Saudi Arabia and the UAE peaked at US$ 6.5 billion in 2008at the height of the global financial crisis. It has since remained relatively high at US$ 4.8 billion annually on average. Total ODA from the three also increased significantly as a share of gross national income, yielding a weighted average of 0.55 percent during 2008-2011, compared to 0.49 percent in the previous four years. The share of Arab financial institutions' aid to International Development Association (IDA) recipients grew by 9 percentage points between 2005-2007 and 2008-2012, reaching 47 percent of total commitments. The overall annual average of financial assistance provided to Arab Spring countries by Arab financial institutions in 2011 and 2012 was slightly higher than the average during the global economic and financial crisis, which in turn was nearly 70 percent higher than the average prior to the crisis. The Gulf countries pledged substantial financial support to the countries undergoing political transitions in the wake of the Arab Spring, but disbursements lagged behind those countries' acute needs. Saudi Arabia has pledged the most funding in this regard.